Analisis Bibliometrik Vosviewer Tutor Sebaya sebagai Learning Organization dalam Pembelajaran - Sumarni, Ria Asep; Dadi, Kanisius Komsiah; Japar, Muhammad; Herdiati, Dian (SAP (Susunan Artikel Pendidikan), 2024)
Several studies on peer tutoring can be analyzed within the framework of learning organization implementation. This study aims to evaluate the role of peer tutoring in education through a bibliometric analysis approach. Using the VOSviewer software, this research identifies and maps the relationships between various concepts related to peer tutoring and Learning Organization. Data was collected in POP using the keyword "peer tutoring" through Google Scholar, resulting in 163 articles published between 2020 and 2024. These were then filtered using the term "Learning Organization," yielding 21 relevant articles, which were saved in RIS format for further analysis using VOSviewer. The analysis results indicate that the term "peer tutoring" is closely linked to concepts such as "learning outcomes," "learning activities," and "learning interest," demonstrating a high relevance in current research. The generated visualization reveals the development of research themes and the interactions between various concepts, emphasizing the important role of peer tutoring in supporting effective learning. This study provides new insights into future research trends, which may focus on a deeper exploration of the relationship between the peer tutoring model and the development of learning organizations, as well as evaluating the effectiveness of peer tutoring in enhancing collaboration skills among learners.